From the inverted classroom to the online lecture hall: Effects on students' satisfaction and exam results. Issue 5 (16th July 2022) - Dahmen, Lena; Schneider, Achim; Keis, Oliver; Straßer, Patrick; Kühl, Michael; Kühl, Susanne J.
Abstract: On‐site teaching at Ulm University was restricted in the summer semester (SS) 2020 due to the Corona pandemic. The biochemistry seminar "From gene to protein" in the 2nd preclinical semester, which had been successfully conducted as an Inverted Classroom (IC), had to be changed to an online concept. The aim of this study was to analyze the concept conversion in terms of students' satisfaction and knowledge acquisition. In the seminar, human medical students of the 2nd semester acquired biochemical and competency‐oriented learning content. In SS2019, the course was taught using the IC concept. For the conversion to the online format in the SS2020, alternative teaching materials were developed and used. Students' satisfaction was assessed by an evaluation questionnaire and knowledge acquisition was tested by a written biochemistry exam. For both teaching concepts a high level of satisfaction was detected. Individual evaluation criteria were evaluated similarly by the students for both concepts. The online concept led up to significantly higher biochemistry exam scores. Due to the high levels of students' satisfaction in both concepts and the results of the biochemistry exam, it can be concluded that online teaching offers a suitable substitute. Based on these results, it is worth to undertake further research on digitization of studies. Abstract :